Odontogenic tumors: A histopathological overview - Sumedha P Shinde; Arvind J Vatkar (MGM Journal of Medical Sciences, 2022)
Introduction: Odontogenic tumors (OTs) are rare and account for around 1% of jaw lesions including tumor and tumor-like lesions. OTs are a diverse category of lesions, displaying different inductive interactions. Although some are hamartomas, others are benign and malignant neoplasms with varying degrees of aggressiveness. Materials and Methods: We plan to review the histopathological aspects of OTs because of their diverse properties. At a tertiary medical and dental institute in Pune, India, we studied 28 cases of OTs over 2 years, from 2013 to 2015. Results: The most common forms of OTs were ameloblastoma (42.86%) and odontogenic keratocyst (21.15%). The highest number of OTs was found in the 21–30-year-old age group, with an even gender distribution. Conclusion: Ameloblastoma is the most common OT, accounting for roughly one-quarter of all jaw tumors. The majority of OTs occurs in young people aged 20–40 years. Fortunately, malignant OTs are extremely rare.